Pengaruh Hipnoterapi dengan Musik Instrumentalia Melayu Jambi dalam Mengatasi Dismenore pada Remaja Putri - Gustina, Gustina; Arifarahmi, Arifarahmi (Universitas Baiturrahim, 2024)
Dysmenorrhea or menstrual pain is a stabbing pain that is felt in the lower abdomen and thighs, this occurs due to an imbalance of the hormone progesterone in the blood, resulting in pain arising. Almost all women have felt interference during menstruation in the form of menstrual pain (dysmenorrhea) with various degrees, ranging from just soreness in the pelvis from the inside to extreme pain. Dysmenorrhea occurs in 50% to 90% of adolescent girls and women of reproductive age and is a major cause of absenteeism. Non-pharmacologically, pain can be treated, one of which is with distraction techniques. The most effective distraction technique to reduce pain is listening to classical music (mozart) and also back exercises. The purpose of the study was to see the influence of hypnotherapy with Jambi Malay instrumental music in overcoming dysmenorrhea in adolescent girls. The research method used a one group experimental questionnaire design by measuring the degree of dysmenorrhea pain using pretest and posttest questionnaires assessing pain scales using the NRS (Numeric Rating Scale. pupolation and sample was 30 female students D 3 Midwifery STIKes Baiturrahim who had dysmenorrhea. The study was conducted September 2022 – September 2023.The results showed a significant influence on the treatment of dysmenorrhea before and after hypnotherapy with Jambi Malay instrumental music with p velue < 000. Conclusion Young women can do hypnotherapy with Jambi Malay instrumental music as local wisdom music, one of the complementary therapy options to overcome dysmenorrhea and it is expected that young women invite peers to be able to do the same in overcoming dysmenorrhoea